Simulation of Quadruple-arc Gear Form Grinding Machining based on VERICUT - Ren Zhongyi; Zhao Yi; Duan Jianzhong (Jixie chuandong)
According to the principle of form grinding,the VERICUT software is used to simulate the machining of quadruple- arc tooth profile gear. Firstly,according to the NC gear grinding machine,the machine tool model,gear blank model is set up and on the basis of the quadruple- arc tooth profile gear form grinding wheel cross- sectional shape,grinding wheel model is established,with reference to the machine tool structure and form grinding motion,NC simulation program is written. Finally,in VERICUT software,the NC simulative machining of quadruple- arc gear is carried on and the simulation results are analyzed. The analysis results show that the simulation process can meet the design requirements,and the numerical control program is correct.